Ustvarjanje pogojev za uresničevanje sprememb - Fifolt, Nina (Revija za univerzalno odličnost, 2025)
Research Question (RQ): How do organizations create conditions for implementing changes? Purpose: To examine the relevant literature addressing various approaches to successful change management in organizations and to establish key findings and insights. Method: In the theoretical part we applied a descriptive method, studying relevant domestic and international literature, and a summarization method by compiling notes and citations from other authors. Our research involved a systematic review of relevant literature, followed by a qualitative analysis in which we identified key findings and insights related to our research question through analytical examination. Results: Organizations create conditions for successfully implementing change through a multidimensional approach influenced by transformational and transactional change factors. The success of change depends on the organization's ability to identify challenges and implement strategies that promote innovation, agility, and stakeholder engagement in organizational processes. The process of change implementation involves continuous self-examination and reflection to achieve excellent results. Open and effective two-way communication, based on transparent evidence, is crucial for reducing barriers to change. Organization: The findings contribute to a better understanding of barriers in change implementation and assist organizations in adopting improved strategies and processes that enhance stakeholder inclusion and foster innovation. Society: Change management not only enhances the success of organizations but can also drive transformative shifts in the external environment, leading to a more innovative and sustainabilityoriented society. Originality: This research provides a comprehensive approach to successful change management by integrating the analysis of strategic (transformational) and operational (transactional) change factors and synthesizing various theoretical models of change management. Limitations/Future Research: The literature analyzed in this research employs various methodologies, which may affect the internal validity of the study. Additionally, the sources encompass organizations from diverse fields, potentially impacting the external validity and generalizability of the findings to other specific sectors. To enhance the validity of research on creating conditions for implementing change, we recommend conducting empirical studies across different sectors.
Keywords: agilnost organizacije; dejavniki sprememb; model EFQM; organizacijska kultura; trajnost; uvajanje sprememb; vodenje sprememb